Diagnostic of lingual tonsil hypertrophy with lateral soft tissue cervical X-ray on laryngopharyngeal reflux - Ade Asyari; Novialdi -; Bonny Murizky; Wahyu Julianda; Esmaralda Nurul Amany; Tuti Handayani; Hafni Bachtiar (Oto Rhino Laryngologica Indonesiana, 2021)
Background: Lingual tonsil hypertrophy (LTH) evaluation could be performed by flexible fiberoptic laryngoscopy, lateral soft tissue cervical X-ray, CT scan, and magnetic resonance imaging (MRI). Lateral soft tissue cervical X-ray examination is considered as a procedure-of-choice for diagnostic testing of LTH, which, aside from being low cost, the examination could also be conducted in all hospitals and easy to be performed on children. Objective: To compare the lingual tonsil enlargement with examination procedure using lateral soft tissue cervical X-ray as an LTH diagnostic measure compared to the flexible fiberoptic laryngoscopy examination as the gold standard examination. Methods: A retrospective analytic study with cross-sectional design on 30 respondents of laryngopharyngeal reflux (LPR) patients who came for routine ENT physical examination, followed by flexible fiberoptic laryngoscopy examination along with lateral soft tissue cervical X-ray. Results: The sensitivity level of 65.38% was acquired from the statistical tests, along with specificity level of 100%, positive predictive value (PPV) of 100%, and negative predictive value (NPV) of 30.37%. Conclusion: Based on sensitivity and specificity, lateral soft tissue cervical X-ray examination could be used as a diagnostic measure and have an accurate capability to diagnose LTH.ABSTRAK Latar belakang: Evaluasi hipertrofi tonsil lingual (HTL) dapat dilakukan menggunakan laringoskopi serat optik fleksibel, foto Rontgen cervical soft tissue lateral, CT scan, dan magnetic resonance imaging (MRI). Foto Rontgen cervical soft tissue lateral dapat dipertimbangkan sebagai pilihan pemeriksaan diagnostik HTL, karena selain biayanya terjangkau, pemeriksaan ini dapat dilakukan di semua rumah sakit serta mudah dilakukan pada pasien anak. Tujuan: Membandingkan hasil pemeriksaan pembesaran tonsil lingual menggunakan foto Rontgen cervical soft tissue lateral dengan pemeriksaan laringoskopi serat optik fleksibel sebagai pemeriksaan baku emas. Metode: Penelitian analitik retrospektif dengan desain potong lintang pada 30 pasien laryngopharyngeal reflux (LPR) yang dilakukan pemeriksaan fisik THT rutin, diikuti dengan pemeriksaan laringoskopi serat optik fleksibel serta foto Rontgen cervical soft tissue lateral. Hasil: Didapatkan tingkat sensitivitas dari uji statistik sebesar 65,38%, dengan tingkat spesitivitas sebesar 100%, dan didapatkan nilai prediksi positif (NPP) sebesar 100% serta nilai prediksi negatif (NPN) sebesar 30,37%. Kesimpulan: Berdasarkan sensitivitas dan spesifisitas, foto Rontgen cervical soft tissue lateral dapat digunakan sebagai alat diagnostik dan memiliki kemampuan yang akurat dalam diagnosis HTL. Kata kunci: hipertrofi tonsil lingual, laryngopharyngeal reflux, laringoskopi serat optik fleksibel, foto Rontgen cervical soft tissue lateral